Monitoring studies of the spread of toxocarosis in dogs in the city of Poltava - H. Pohorelova (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2023)
Most types of helminths are widespread in many countries and severely threaten human health. One of the most dangerous zooanthropohelminthiases is toxocarosis. The causative agent of toxocarosis – the nematode Toxocara canis in the imaginal stage parasitizes in the small intestine of carnivores and the larval stage (Visceralis larva migrans) – in various organs and tissues of animals and humans. Toxocarosis has both veterinary and social significance. Toxocara canis larvae can migrate in the human body and cause various pathologies: hepatitis, encephalitis, chorioretinitis. The purpose of the research was to analyze data from the reporting documentation of the Poltava Veterinary Center regarding the prevalence of toxocarosis among the domestic dog population. According to the results of the analysis of the statistical data of the reporting documentation of the veterinary center of the Shevchenkivskyi district of the city of Poltava for 2019–2022, it was established that the average infestation of dogs by the causative agent of toxocarosis in the territory of the city of Poltava is 22.89 %, with a range from 17.51 to 28.02 %. The share of toxocarosis in the total parasitic pathology diagnosed in dogs was 27 %. The mestizos were the most affected by the causative agent of toxocarosis, where the extent of invasion was 29.26 %. A lower rate of toxocares was found in dogs of decorative (24.05 %), service (21.24 %), and hunting (18.56 %) breeds. In particular, the highest values of the extent of infestation were found in Yorkshire terriers (39.71 %). Less often, toxocarosis was diagnosed in toy terriers (extent of infestation – 19.12 %), English cocker spaniels (19.83 %), dachshunds (18.03 %), pugs (16.37 %), Jack Russell terriers (15.82 %) and pickiness (12.6 %). Seasonal dynamics of toxocarosis in dogs are characterized by the peak of invasion in the spring and autumn periods, where the infection rates of animals were at 35.0 and 30.0 %, respectively. The extent of toxocarosis infestation declined in winter – by 12.0 %. The obtained data indicate the relevance of the problem of toxocarosis as a zooanthroponous invasion in connection with the significant damage to domestic dogs by toxocares in the city of Poltava.